Attachment and Adjustment in Adolescents and Young Adults With a History of Pediatric Functional Abdominal Pain. Issue 2 (February 2015) - Laird, Kelsey T.; Preacher, Kristopher J.; Walker, Lynn S.
Abstract : Objectives: This study tested predictions of the Attachment-Diathesis Model (ADM) of Chronic Pain in a cross-sectional sample of adolescents and young adults with a history of childhood functional abdominal pain (FAP). ADM posits that attachment anxiety is a diathesis for poor adjustment (physical health, mental health, and functioning) in the context of chronic pain and that pain self-efficacy, pain threat appraisal, and passive coping mediate this effect. Methods: Participants (N=261) were recruited from a database of consecutive new patients evaluated for abdominal pain at a pediatric gastroenterology clinic. Participants' mean age at the follow-up assessment was 21 years. Structural equation modeling was used to test the fit of our conceptual model to the data. Results: Model fit was good (comparative fit index=0.971, the Tucker-Lewis index=0.940, root mean square error of approximation=0.067). Attachment anxiety significantly predicted poorer health in both the mental and physical domains. Model fit was consistent with our hypothesis that pain self-efficacy mediates the effect of attachment anxiety on passive coping and that passive coping, in turn, mediates the effect of pain self-efficacy and pain threat appraisal on mental and physical health. Discussion: Among individuals with a childhood history of FAP, those with anxious attachment may be at higher risk for poor physical and mental health. Pain beliefs and coping may mediate the relation between anxious attachment and health outcomes and may serve as effective targets for intervention in chronic pain.